If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(x) + 6x + 4 = 0 Multiply X * x xX + 6x + 4 = 0 Reorder the terms: 4 + 6x + xX = 0 Solving 4 + 6x + xX = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + 6x + -4 + xX = 0 + -4 Reorder the terms: 4 + -4 + 6x + xX = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 6x + xX = 0 + -4 6x + xX = 0 + -4 Combine like terms: 0 + -4 = -4 6x + xX = -4 Reorder the terms: 4 + 6x + xX = -4 + 4 Combine like terms: -4 + 4 = 0 4 + 6x + xX = 0 The solution to this equation could not be determined.
| x-0.95=-3.6 | | x^2+2x=36 | | 25+4y-20=19y-10 | | 6x+32=11x-3 | | -4x+8y=56 | | X-2+x-2+x-2=294 | | 3x-8=8-33 | | -6y+5=-12 | | x-2=4-2 | | 4(n+2)(n+5)=0 | | 3q^2=-5 | | 0.4+2=24 | | 4x=log(3)8x-2 | | 10y=-20 | | -6-x=0 | | 3x=(78,6*5)2 | | x=(78,6*5)2 | | y-4=5 | | k^2-3k=10 | | 3z-2z-6= | | 15-4(x-3)=x-3 | | 13+9x=-21x-17 | | 3z-2z+6= | | 7x-4=3x+2(x+3) | | -5-5y=-20 | | 0-5y=-20 | | z+2=10 | | 5m+10n= | | 9=6-2x | | 12+4y=8 | | -3(x-1)+2x=10 | | 2x^2+3x=6 |